Upaya Peningkatan Mutu Sekolah melalui Satuan Otonomi Pendidikan - Ade Cahyana (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
The diversity of school environtment conditions and student needs in learning process alongside with the complexity in Indonesia geographical condition quite often can not be easily concluded completely in one piece by the central bureaucracy in a comprehensive way. It stimulates the deliverance of school based quality management improvement. This type of alternative management empowers independency to school to initiate its self-governing capacity to manage its own activities in the framework of eduactional quality improvement, while consistently aligned to national policies. Some of the strategies applied at schools comprise self-evaluation to scrutinize the schoolâ€™s strengths and weaknessses. On the basis of the evaluation, school alongside with parents and community settleon school vision and mission of education quality improvement or to put together the expected eduaction quality for further developing on the planning of school program which includes school financing by refering to the scale of priorities and national policies in corresponding to the school condition and the capacity of its human resources. The consequences of the program implementation should imply a highly committed engagement among diversified parties, i.e., parents/community, teachers, principals, pupils and other staffs on one hand, and government (MONE) on the other hand, as the equal partner to attain the objective of quality improvement.Â ABSTRAKBeragamnya kondisi lingkungan sekolah dan bervariasinya kebutuhan siswa di dalam proses pembelajaran ditambah lagi dengan kondisi geografi Indonesia yang sangat kompleks, seringkali tidak dapat diapresiasikan secara lengkap oleh birokrasi pusat. Oleh karena itu, dalam proses peningkatan mutu pendidika perlu dicari alternatif pengelolaan sekolah. Hal ini mendorong lahirnya konsep manajemen peningkatan mutu berbasis sekolah. Manajemen alternatif ini memberikan kemandirian pada sekolah untuk mengatur dirinya sendiri dalam rangka peningkatan mutu pendidikan, tetapi masih tetap mengacu pada kebijakan nasional. Konsekwensi dari pelaksanaan program ini antara lain komitmen yang tinggi dari berbagai pihak yaitu: orang tua/masyarakat, guru, kepala sekolah, siswa dan staf lainnya di satu sisi dan pemerintah (Kemendiknas) di sisi lainnya sebagai mitra dalam mencapai tujuan peningkatan mutu.